Long-term visuospatial retention unaffected by fornix transection. - Kwok, S; Buckley, M (2010)
As part of an earlier experiment (Kwok and Buckley, 2009), six macaque monkeys (three with fornix transection and three unoperated controls) were trained postoperatively to discriminate a total of 104 new concurrent visuospatial conditional problems to criterion. Our experiment measured and compared long-term retention of these problems with two separate one-trial postoperative retention tests administered 3 and 15 months, respectively, after acquisition. All animals showed some degree of forgetting of these problems but all remembered above chance levels, even after 15 months. The amount forgotten by each group did not differ significantly at either time point. These results show that long-term retention of visuospatial information is independent of the fornix. Similarities in resistance to forgetting are drawn between fornix-transected macaques and patients with amnesia and the implications for clinical rehabilitation are discussed.